THE INFLUENCE OF MOTIVATION, WORKLOAD AND COMPETENCY ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE IN THE RIAU ISLANDS PROVINCIAL HEALTH OFFICE - Susilo Budi Hartanto; Ngaliman; Sri Yanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
In this study, researchers variables Motivation, Workload, Competence, Organizational Commitment and Employee Performance. Data analysis with parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling-Partial Least Square) Data analysis with parametric and non-parametric statistics regarding research variables, calibration test / pilot test, validity and reliability, Outer model and inner model analysis, as well as a discussion of the results of hypothesis testing or Path Analysis Path. This study uses path analysis to examine the pattern of relationships that reveals the effect of a variable or set of variables on other variables, both direct and indirect. The calculation of the path coefficient in this study was assisted by SmartPLS Ver 4.0 2022. The results of this study indicate a direct influence that Motivation, Workload and Competence variables have a significant positive effect on Organizational Commitment. Organizational Commitment and Motivation have a significant positive effect on Employee Performance. Workload has a positive insignificant effect on Employee Performance. Competence has a positive insignificant effect on Employee Performance. Organizational Commitment has a significant positive effect in mediating Motivation on Employee Performance. Organizational Commitment has a positive and significant effect in mediating Workload on Employee Performance. Organizational Commitment has a negative and insignificant effect in mediating Competence on Employee Performance.